Could a playful approach to teaching be a path to resonant connections? Experiences from teacher education in Denmark - Skovbjerg, Helle Marie; Jensen, Julie Borup (Frontiers in Education, 2024)
Creative and playful approaches to teaching in teacher education emerge these years. Due to the increasing focus on performance, pace, visible goals, and efficiency in the educational systems within the Western societies, there seem to be a search for new answers when organising teaching within teacher education -also for the future. Based on empirical material created in a large research project in teacher education in Denmark, this paper analyses how playful approaches can contribute to improving conditions for a holistic approach to education, and how these approaches must be linked to concrete pedagogical actions. By applying a theoretical framework of playful approaches to learning in teacher education based on Rosa (2020), Lennon (2015) and xxx (2021), the main contribution of the paper is to point to both pedagogical directions and clarifications when working with playful approaches in teacher education.